PEMBUKTIAN MENS REA DALAM TINDAK PIDANA PENCUCIAN UANG BAGI PELAKU PASIF - Zaki, Ahmad; Effendi, Erdianto; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Cultural heritage is a nation's indispensable identity to promote Indonesia's national culture. Cultural heritage includes the culture of tangible cultural heritage and intangible cultural heritage. Indonesia's cultural heritage that has been registered and managed by the Directorate General of Culture to date has amounted to 594 cultural works. The cultural work consists of 137 people's customs, rites and celebrations; 160 works of traditional skills and crafts; 31 cultural works in the field of knowledge and behavioral habits concerning the universe; 69 in the field of tradition and oral expression, as well as 197 cultural works related to performing arts. Silek Lintau is one of the performing arts. Currently Silek Lintau is more popular in foreign country than in Indonesia, so Silek Lintau needs to be protected.This study uses a sociological legal research typology or so-called non-doctrinal legal research, more specifically discussing the effectiveness of the law. In this study the author uses the nature of descriptive research, because the authors describe Implementation of Unesco Convention For The Safeguarding Of The Intangible Cultural Heritage 2003 In Protecting Silek Lintau. The results of the research conducted by the author is, first Silek Lintau can be protected internationally through Convention UNESCO Convention For The Safeguarding Of The Intangible Cultural Heritage 2003. Besides can be protected through the Regime of UNESCO 2003, Silek Lintau can also be protected through Intellectual Property Rights Regime, at UNESCO Convention On The Protection And Promotion Of The Diversity Of Cultural Expression 2005. Central and local governments are obliged to advance the culture of the Indonesian nation. In protecting the culture, there are various obstacles, including the erosion of cultural values due to lack of appreciation from the younger generationKeywords: Protection - International - Silek Lintau - UNESCO Convention